IMPROVING THE SPECIAL PHYSICAL INDICATORS OF FREESTYLE WRESTLERS THROUGH THE ANNUAL TRAINING CYCLE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The study analyzes the effectiveness of the annual training cycle in enhancing the special physical preparation of freestyle wrestlers. It highlights the role of scientifically based training methodologies aimed at developing athletes’ physical qualities. Throughout the research, the preparation processes of wrestlers before competitions, the distribution of workloads at different stages of the annual training cycle, and the effectiveness of training methods are evaluated. The findings provide practical recommendations aimed at further improving the athletes’ physical readiness and boosting their competitive results